2017
DOI: 10.20471/acc.2017.56.03.15
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Transmission of Violence among Parents of Preschool Children in Croatia

Abstract: The aim of this study was to determine whether there is a transgenerational transmission of violence within the family on a sample of parents of preschool children in Croatia, and to identify the factors that increase the likelihood of child abuse. The Child Abuse Questionnaire was self-administered to the sample of 118 parents of preschool children (91 mothers and 27 fathers) during February 2013. There were 7.7% of mothers and 3.8% of fathers who answered that they slapped their child, while 15.4% of the fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…Studies included in this review varied greatly in terms of their methodological quality. Some studies obtained very low ratings using AXIS (i.e., Adshead & Bluglass, 2005; Faller, 1989; Korbin, 1986; Rikić et al, 2017; Zuravin & Fontanella, 1999) while others obtained high ratings (i.e., Clément & Bouchard, 2003; Clément et al, 2012; Putnam-Hornstein, Cederbaum, King, Eastman, & Trickett, 2015). The main limitations from the included studies in terms of design, sample, and measures are described here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies included in this review varied greatly in terms of their methodological quality. Some studies obtained very low ratings using AXIS (i.e., Adshead & Bluglass, 2005; Faller, 1989; Korbin, 1986; Rikić et al, 2017; Zuravin & Fontanella, 1999) while others obtained high ratings (i.e., Clément & Bouchard, 2003; Clément et al, 2012; Putnam-Hornstein, Cederbaum, King, Eastman, & Trickett, 2015). The main limitations from the included studies in terms of design, sample, and measures are described here.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies obtained very low ratings using AXIS (i.e. Adshead, & Bluglass, 2005;Faller, 1989;Korbin, 1986;Rikić et al, 2017;Zuravin & Fontanella, 1999) while others obtained high ratings (i.e. Clément, & Bouchard, 2003;Clément et al, 2012;Putnam-Hornstein et al, 2015).…”
Section: Prevalence Of the It/c Of Child Maltreatmentmentioning
confidence: 99%
“…Evidence of that appears in a Brazilian study that points out that men perceive themselves reproducing in their marital status the same violent attitudes enacted by their parents (3) . Another study conducted in Croatia, on the other hand, shows a female perception that they experience with their partners the same situations of violence suffered by their mothers (4) .…”
Section: Introductionmentioning
confidence: 97%
“…The literature suggested the possibility of the intergenerational transmission of violence (Black et al, 2010 ; Lünnemann et al, 2019 ). In fact, children who have been exposed to, or witnessed, parental violence seem to be at higher risk of exhibiting violent behaviors toward both their partner and descendants in the future (Rikić et al, 2017 ). In a 20-year prospective study, Ehrensaft et al ( 2003 ) showed that witnessing domestic violence between caregivers (e.g., parents and guardians) may contribute to adopting similar (dysfunctional) ways of managing conflicts with loved ones in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it may also be possible that caregivers themselves had been traumatized by the dysfunctional relational styles of their own parents and that this traumatic experience remains unelaborated (Cusinato, 2013 ; Rikić et al, 2017 ). Similarly, the unresolved traumatic experiences of parents may be projected to and then internalized by their children who may be at risk to manifest them in their own future relationships (Fonagy, 1999 ; Roitman, 2017 ; Stob et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%